2017
DOI: 10.1093/hmg/ddx079
|View full text |Cite
|
Sign up to set email alerts
|

PNPLA1 defects in patients with autosomal recessive congenital ichthyosis and KO mice sustain PNPLA1 irreplaceable function in epidermal omega-O-acylceramide synthesis and skin permeability barrier

Abstract: Autosomal recessive congenital ichthyosis (ARCI) is a heterogeneous group of monogenic genodermatoses that encompasses non-syndromic disorders of keratinization. The pathophysiology of ARCI has been linked to a disturbance in epidermal lipid metabolism that impaired the stratum corneum function, leading to permeability barrier defects. Functional characterization of some genes involved in ARCI contributed to the identification of molecular actors involved in epidermal lipid synthesis, transport or processing. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 49 publications
0
55
0
Order By: Relevance
“…A recent breakthrough in this research area has been the identification of PNPLA1, a member of the iPLA 2 family, as a long-sought ω-O-acylceramide synthase, whose genetic mutations in humans and dogs cause congenital [56] and deletion in mice leads to neonatal death due to excessive transepidermal dehydration resulting from severe skin barrier defect [57][58][59]. PNPLA1 catalyzes the unique transacylase reaction, whereby the LA moiety cleaved from triacylglycerol through the lipase-like reaction of this enzyme is directly transferred to the ω-hydroxy moiety of ultra-long chain fatty acid in ceramide (ω-O-hydroxyceramide), with the ω-hydroxy group, instead of water, serving as an acyl (linoleoyl) acceptor [60].…”
Section: Pnpla1 An ω-O-acylceramide Synthase (Transacylase)mentioning
confidence: 99%
“…A recent breakthrough in this research area has been the identification of PNPLA1, a member of the iPLA 2 family, as a long-sought ω-O-acylceramide synthase, whose genetic mutations in humans and dogs cause congenital [56] and deletion in mice leads to neonatal death due to excessive transepidermal dehydration resulting from severe skin barrier defect [57][58][59]. PNPLA1 catalyzes the unique transacylase reaction, whereby the LA moiety cleaved from triacylglycerol through the lipase-like reaction of this enzyme is directly transferred to the ω-hydroxy moiety of ultra-long chain fatty acid in ceramide (ω-O-hydroxyceramide), with the ω-hydroxy group, instead of water, serving as an acyl (linoleoyl) acceptor [60].…”
Section: Pnpla1 An ω-O-acylceramide Synthase (Transacylase)mentioning
confidence: 99%
“…Furthermore, results inconsistent with the current line of thinking come from inactivation studies with PNPLA1, the gene that esterifies linoleate to CerOS, forming CerEOS (21)(22)(23)(24)(25). In Pnpla1-deficient mice or patients with mutations in the PNPLA1 gene, the CLE is almost absent even though CerOS and its glucosylated form are highly accumulated (22,24,25). This suggests that the prerequisite for lipoxygenase-catalyzed oxidation of CerEOS is not in order to facilitate de-esterification of the linoleate moiety and produce CerOS, but rather has a different functional role during formation of the CLE.…”
Section: Introductionmentioning
confidence: 81%
“…However, the transglutaminase(s) are not identified, and known gene knockouts do not exhibit the expected skin phenotype with absence of the CLE (19,20). Furthermore, results inconsistent with the current line of thinking come from inactivation studies with PNPLA1, the gene that esterifies linoleate to CerOS, forming CerEOS (21)(22)(23)(24)(25). In Pnpla1-deficient mice or patients with mutations in the PNPLA1 gene, the CLE is almost absent even though CerOS and its glucosylated form are highly accumulated (22,24,25).…”
Section: Introductionmentioning
confidence: 98%
“…Some of them have been addressed in many works which demonstrated their involvement in stratum corneum lipid metabolism. Recently, our group as well as others showed that PNPLA1 was a key player in the formation of v-esterified ceramides (Grond et al, 2017;Hirabayashi et al, 2017;Ohno et al, 2017;Pichery et al, 2017).…”
Section: Epidermal Barrier and Stratum Corneum Lipids: Importance Of mentioning
confidence: 88%